2021
DOI: 10.1038/s41467-020-20577-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting adaptor protein SLP76 of RAGE as a therapeutic approach for lethal sepsis

Abstract: Accumulating evidence shows that RAGE has an important function in the pathogenesis of sepsis. However, the mechanisms by which RAGE transduces signals to downstream kinase cascades during septic shock are not clear. Here, we identify SLP76 as a binding partner for the cytosolic tail of RAGE both in vitro and in vivo and demonstrate that SLP76 binds RAGE through its sterile α motif (SAM) to mediate downstream signaling. Genetic deficiency of RAGE or SLP76 reduces AGE-induced phosphorylation of p38 MAPK, ERK1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…The study by Yan et al shed light on the development of LCP2-targeted therapeutics for sepsis and revealed the important function of LCP2 in RAGE-mediated proinflammatory signaling. 22 The immune system plays a critical role after tumor occurrence, and tumor development is a multi-gene and multi-stage process that includes important contributions of oncogenes and tumor suppressor genes. Thus, the role of LCP2 in LUAD cells and the tumor microenvironment still needs to be further explored in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Yan et al shed light on the development of LCP2-targeted therapeutics for sepsis and revealed the important function of LCP2 in RAGE-mediated proinflammatory signaling. 22 The immune system plays a critical role after tumor occurrence, and tumor development is a multi-gene and multi-stage process that includes important contributions of oncogenes and tumor suppressor genes. Thus, the role of LCP2 in LUAD cells and the tumor microenvironment still needs to be further explored in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…CLP was performed to induce sepsis in mice as previously described [ 23 , 24 ]. In brief, The mice were anesthetized with 2% isoflurane and fixed on a 37 °C operating platform.…”
Section: Methodsmentioning
confidence: 99%
“…The operation details for the PlexArray HT were as described previously. 65 The purified protein samples were prepared at determined concentrations in PBS running buffer, while glycine-HCl buffer (10 mmol/L, pH 2.0) was used for regeneration. Binding data were collected and analyzed by SPR Data Analysis Module software (Plexera, USA).…”
Section: Methodsmentioning
confidence: 99%